An Analysis of the Implementation of Green Building Technologies in Reducing Energy Consumption and Their Impact on Corporate Performance in Jakarta - Dila Padila Nurhasanah; I Wayan Karang Utama; Rival Pahrijal (Westscience Press, 2026)
This study aims to analyze the effect of green building technology implementation on energy consumption reduction and its impact on company performance in Jakarta. A quantitative research design was employed using data from 150 respondents who are involved in building operations, facility management, and sustainability-related functions. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that green building technology has a significant positive effect on energy consumption reduction. In addition, energy consumption reduction significantly improves company performance through cost efficiency and operational effectiveness. The findings also show that green building technology has a direct positive effect on company performance. Furthermore, energy consumption reduction partially mediates the relationship between green building technology and company performance. The study concludes that the adoption of green building technologies plays a strategic role in improving both environmental efficiency and organizational performance in urban corporate settings.